Pengaruh Pakan Komersial Terfermentasi EM4 terhadap Pertambahan Bobot Badan, Konsumsi Pakan, dan Konversi Pakan Ayam Broiler - Imelda Boki (Program Studi Peternakan, Fakultas Pertanian, Universitas Timor, 2020)
The aim of this study was to determine the effect of EM4 fermentation at commercial feed on body weight gain, feed intake and feed conversion ratio of broilers. This study was conducted at Kefamenanu, Timor Tengah Utara from April to May 2019. A total of 80 days-old chickens (DOC) were used in this study. The experiment was designed as a Completely Randomized Design (CRD), consisting of 4 treatments and 4 replications. The DOC were divided into 4 treatments groups with 4 replications. The treatment diets were: R0 (commercial feed as control),R1 (EM4 fermentation 5 ml/kg commercial feed), R2 (EM4 fermentation 10 ml/kg commercial feed), R3 (EM4 fermentation 15 ml/kg commercial feed). The data collected were body weight gain, feed intake and feed conversion ratio of broilers. The results of statistical analysis showed that EM4 fermentation at commercial feed gave effected (P<0.05) upon body weight gain, feed intake and feed conversion ratio of broilers. It can be concluded that maintenance of broilers can give EM4 fermentation 5 ml/kg commercial feed.